Effectiveness of Strength Training among Post Covid Subjects in Activities of Daily Living. - Minu R.; Rekha K.; J., Saravan Kumar; Preethi G.; Kabilan R. (Indian Journal of Physiotherapy & Occupational Therapy)
Background: The current COVID 19 caused by severe acute respiratory syndrome. COVID 19 is not limited to the respiratory system but has widespread involvement. Some specific problems are described, including severe muscle weakness and fatigue, joint stiffness, dysphasia, psychological problems, impaired functioning concerning mobility, activities of daily life and work get affected. Rehabilitation care for COVID-19 survivors must therefore be delivered by specialist multidisciplinary team, need focused and planned for the longer term to meet the needs of these individuals. Purpose: To evaluate the effect of strength training exercise and conventional care on levels of dyspnea and post COVID functional levels among post COVID-19 participants. Materials and Methods: 30 individuals diagnosed with post COVID-19 were selected based on the inclusion and exclusion criteria. Post COVID-19 patients were selected from the inpatient ward, Saveetha hospital. The selected subjects were allocated into 2 groups. Strength training group and conventional group. Strength training group were treated with diaphragmatic strength training and conventional group was treated with thoracic mobility exercise. The effectiveness of the treatment was assessed at the end of 6 weeks, using various outcome measures. Conclusion: We conclude, Diaphragmatic strength training exercise has better impact in improving in functional levels among post COVID-19.